2018
DOI: 10.1080/15623599.2018.1435155
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the selection of delay analysis methods in construction projects in UAE

Abstract: The aim of the Leeds Beckett Repository is to provide open access to our research, as required by funder policies and permitted by publishers and copyright law. The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team. We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Factors influencing the selection of delay analysis method [129], UAE, a hotel, an international school complex, a highway, sewage treatment plant, and a residential tower Interviews; 8; experts; limited to case studies in the period of 2007-2012…”
Section: Method; Sample Size and Participants Number Of Factors Measumentioning
confidence: 99%
“…Factors influencing the selection of delay analysis method [129], UAE, a hotel, an international school complex, a highway, sewage treatment plant, and a residential tower Interviews; 8; experts; limited to case studies in the period of 2007-2012…”
Section: Method; Sample Size and Participants Number Of Factors Measumentioning
confidence: 99%
“…Use of non-conforming analysis for delay or computational errors leads to emergence of irrecoverable factors for stakeholders and the project, where, creation of a specialized structure and mechanism, development of new technical methods and instructions are necessary to solve these problems (Yazeed et al , 2018). In the article Causes of delays in construction industry and comparative delay analysis techniques with SCL protocol, They sought to discover the root causes of project delays with the help of the SCL Protocol and the International Association for the Development of Value Engineering (AACEI).…”
Section: Literaturementioning
confidence: 99%
“…Delays growth in UAE and Saudi Arabian projects is 39%. Research has shown that deciding on project delays is a very important factor affecting business investors (Yazeed et al , 2018). In an article entitled “From Risk Matrices to Risk Networks in Construction Projects,” there is a way to control risk.…”
Section: Introductionmentioning
confidence: 99%
“…Source selection is intrinsically a multi-criteria decision-making process and has been surveyed by many researchers. Although collaborative pre-contract planning can significantly reduce the risk of project failure [1,2], selection of qualified sources is still a critical issue that has major impacts on the project's success and indeed is a risk that should be managed in an appropriate way [2][3][4][5]. This decision and procurement efforts more generally have been considered as a pivotal factor of project success [6].…”
Section: Introductionmentioning
confidence: 99%